1999
DOI: 10.1002/j.1551-8833.1999.tb08622.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting full‐scale TOC removal

Abstract: A Langmuir model providing good prediction of full‐scale TOC removal during enhanced coagulation may help utilities comply with forthcoming regulations. A Langmuir model provides the best available prediction of full‐scale removal of total organic carbon (TOC) during enhanced coagulation. Because jar tests allow more transfer of carbon dioxide gas than treatment plants, the model can even correct certain errors arising during such tests. When the model was adapted to predicting TOC removal in two raw water sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…Dempsey (1989) concluded that ADS is the predominant mechanism for alum coagulation of fulvic acids at all pH levels, although he did not discount the possible significance of polymeric aluminum species. These conclusions are consistent with the view of others who have found that ADS as the primary mechanism for NOM removal is consistent with practical observations (Dennett et al, 1996;Edwards, 1997;Tseng and Edwards, 1999).…”
Section: Adsorptionsupporting
confidence: 93%
“…Dempsey (1989) concluded that ADS is the predominant mechanism for alum coagulation of fulvic acids at all pH levels, although he did not discount the possible significance of polymeric aluminum species. These conclusions are consistent with the view of others who have found that ADS as the primary mechanism for NOM removal is consistent with practical observations (Dennett et al, 1996;Edwards, 1997;Tseng and Edwards, 1999).…”
Section: Adsorptionsupporting
confidence: 93%
“…Previous studies showed that the traditional coagulants (alum and ferric salt) provide optimal organic matter removal at low pH values (pH < 6.0). TOC removal for high alkalinity water is generally obtained by acidifying the raw water with H 2 SO 4 or by applying increased dose of hydrolyzing coagulants (USEPA, 1998;Crozes et al, 1995;Tseng and Edwards, 1999). Unfortunately, both of these methods can increase the corrosivity of water, or the dose of base required to counter the corrosive tendency of water before water distribution (Carlson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several empirical and semi‐empirical models have been proposed and have been used in prediction of DOC removal during coagulation (van Leeuwen et al, 2003; Edwards, 1997; Harrington et al, 1992; Moomow et al, 1992). Tseng and Edwards (1999) showed that the most accurate predictions of final DOC by enhanced coagulation were demonstrated in a model developed by Edwards (1997) that assumed the following: DOC removal is mainly the result of adsorption onto metal hydroxide flocs formed during coagulation. There exists a nonsorbable fraction that is not amenable to coagulation by the metal coagulant considered. The adsorption can be described by the Langmuir isotherm. The adsorption capacity of the floc is a function of pH. The characteristics of organic matter do not change with pH. …”
mentioning
confidence: 99%